Effects of xylanase in growing-finishing diets varying in dietary energy and fiber on growth performance, carcass characteristics, and nutrient digestibility - Barnes, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 576 pigs (PIC TR4 × 1050, 106 lb initial BW) were used in a 75-d trial to evaluate effects of xylanase (Porzyme 93010; Danisco Animal Nutrition, St. Louis, MO) in growing-finishing diets varying in dietary energy and fiber on growth perfor- mance, carcass characteristics, and nutrient digestibility. Pens of pigs were randomly allotted to 1 of 6 dietary treatments in a 2 × 3 factorial (with or without xylanase and 3 dietary energy levels) with 8 pigs per pen and 12 replications per treatment. The 6 treatments consisted of corn-soybean meal-based diets with added dried distillers grains with solubles (DDGS), wheat middlings (midds), and choice white grease (CWG) arranged to make low- (30% DDGS, 12.5% midds, and 0% CWG), medium- (15% DDGS, 6.25% midds, and 1.2% CWG), and high-energy diets (0% DDGS, 0% midds, and 2.4 % CWG) with or without xylanase (0 or 4,000 units xylanase per kilogram of diet). Diets were formulated to contain increasing dietary CWG in the medium- and high-energy treatments to maintain uniform dietary crude fat levels. All diets were fed in meal form and in 4 phases. No xylanase × energy interactions (P ≥ 0.06) occurred for any criteria evaluated. Overall (d 0 to 75), pigs fed diets with xylanase had poorer ADG (P < 0.02) compared with pigs fed diets without added xylanase. No differences were found in any other growth response criteria between pigs fed diets with or without xylanase. Pigs fed diets with increasing energy had improved (linear; P < 0.001) ADG and F/G with no effect on ADFI. For carcass traits, increasing energy improved carcass yield (linear; P < 0.01) and HCW (linear; P < 0.001), but increased backfat depth (linear; P < 0.01). Furthermore, pigs fed diets with increasing energy had lower lean percentage (linear; P < 0.003) and jowl fat iodine value (IV) (linear; P < 0.001). Apparent fecal digestibility of ADF improved (P < 0.002) with the addition of dietary xylanase; however, there were no differences in any other nutrient digestibility criteria evaluated. As dietary energy increased, apparent digestibility of DM, N, fat, GE, ADF, and NDF increased (linear, P < 0.02). Feeding pigs diets with increasing energy levels resulted in improved performance over those fed low-energy diets. Although ADF digestibility was increased with xylanase supplementation, growth performance, carcass characteristics, and other nutrient digestibility values did not improve.
Keywords: Swine; Fiber; Finishing pig; Zylanase